Assessment of the integrative pediatric care competence in pediatric interns - Galina Galceran Chacón; Luis Aníbal Alonso Betancourt; Prudencio Alberto Leyva Figueredo (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Pediatrics is the branch of General Medicine that is responsible for the study of the conditions of the internal systems of children and adolescents, as well as their prevention and treatment through personal and continuous care, with an integral conception of the individual as a biological, psychic and social unit, in order to provide solutions to a large number of medical problems defined for their care. Objective: To evaluate the competence for integrative pediatric care in pediatric residents. Material and Methods: A quantitative research, of pre-experimental, observational, transversal type was carried out from a sample of 26 residents of the Pediatric Specialty Program of the University of Medical Sciences of Holguin, assuming simple random probability sampling. Results: The profile of the integrative pediatric assistance competence that singles out the Pediatrician's assistance function and the instrument for its evaluation were provided. Improvements were found in the care performance of the residents by proposing innovative alternatives to solve health problems in pediatric patients. Conclusions: The competence of integrative pediatric assistance expresses the integration of knowledge that allows the pediatrician, from a holistic vision, to solve health care problems of pediatric patients in which the clinical, epidemiological and investigative methods are integrated, taking into account the social complexities and the management of sexuality in view of the new projection of current times, addictions, as well as environmental and social changes of the family and community environment and their impact on the health-disease process in pediatric ages.